Estimativas de fronteira para problemas elípticos de perturbação singular na teoria de combustão - Silva, José Gleison Carneiro da (2016)
In this work we study up to the boundary Lipschitz estimates for classes of singular perturbation problems appearing in the combustion theory in the study of flame propagation issues. Here we study problems involving the fully nonlinear equation and quasilinear type equations both involving unbounded force terms (RHS).